A heuristic for fault-tolerance provisioning in multi-radio hybrid wireless-optical broadband access network - Schutz, G. (2013)
The wireless-optical broadband-access network (WOBAN) architecture has been proposed as a flexible and cost-effective solution for future access networks. However, for WOBANs to provide geographically continuous wireless coverage it is necessary to integrate fault-tolerance in the design of such networks. In this paper we develop a heuristic algorithm to solve the problem of planning a wireless and optical fault-tolerant multi-radio WOBAN, considering any fault-tolerance scenario (e.g. some nodes/links/region only), while making an efficient reuse of spectrum.